(untitled) (Global Journal of Science Frontier Research, 2019)
This article presents research data of the kinetics of Saccharomyces cerevisiae yeasts aerobic cultivation without forced air supply to the cultivator. Oxygen penetrates into the culture medium through its free surface and spreads throughout the liquid volume only due to molecular diffusion. Culture medium mixing occurs with pop-up bubbles of carbon dioxide and thermal energy released by the cells during their development.